2020
DOI: 10.1038/s41598-020-57996-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of genetically engineered mice with higher efficiency, lower mosaicism, and multiplexing capability using maternally expressed Cas9

Abstract: The CRISPR/Cas9 system is widely used to generate gene-edited animals. Here, we developed an efficient system for generating genetically modified mice using maternal Cas9 from Cas9 transgenic mice. Using this system, we achieved lower mosaicism and higher rates of knock-in success, geneediting, and birth compared to the similar parameters obtained using exogenously administered Cas9 (mRNA/protein) system. Furthermore, we successfully induced simultaneous mutations at multiple loci (a maximum of nine). Our nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Others include a 103 ssODN donor targeting the Fgf10 gene (Hashimoto et al, 2016), and a 128 bp oligonucleotide targeting the Aicda gene (Wang et al, 2016). Sakurai et al (2020) utilized oocytes from transgenic mice expressing maternal Cas9 (maCas9) to generate gene-edited embryos and pups. The group compared mutation rates between embryos and pups following zygote transfections either with gRNA alone or with both Cas9 and gRNA.…”
Section: Electroporation Of Donor Repair Nucleic Acid Sequencesmentioning
confidence: 99%
“…Others include a 103 ssODN donor targeting the Fgf10 gene (Hashimoto et al, 2016), and a 128 bp oligonucleotide targeting the Aicda gene (Wang et al, 2016). Sakurai et al (2020) utilized oocytes from transgenic mice expressing maternal Cas9 (maCas9) to generate gene-edited embryos and pups. The group compared mutation rates between embryos and pups following zygote transfections either with gRNA alone or with both Cas9 and gRNA.…”
Section: Electroporation Of Donor Repair Nucleic Acid Sequencesmentioning
confidence: 99%
“…This is in contrast to the case of genome-edited mice. For instance, since Kaneko et al [21] first reported the successful use of this technology in 2014, several genome-edited mice have been produced by numerous laboratories worldwide [22][23][24][25][26][27][28][29][30][31][32][33][34]. Tanihara et al [13] pioneered in demonstrating in vitro EP as a promising tool for producing GM piglets with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of the GM animals developing mutations (or transgene insertion) only in one allele, obtaining homozygous knock out (KO) animals is time-consuming (at least >0.5 years in the case of pigs) and cumbersome [35]. In mice, in vitro EP is beneficial for producing animals with bi-allelic KO phenotypes with relatively high efficiency, as the GECs are incorporated into the embryo with lesser bias [34]. This is in contrast with the findings of our previous work, in which a cytoplasmic injection administered to obtain genome-edited porcine embryos resulted in frequent mosaic mutations in the target locus [36].…”
Section: Introductionmentioning
confidence: 99%
“…Maternally contributed Cas9 protein within the fertilized zygote is sufficient for mutagenesis, and only the sgRNA and repair template need be introduced. Indeed, maternally supplied Cas9 was found to result in a more consistent and efficient mutagenesis 14 , 16 . In this study we extend our side-by-side comparison of delivery methods to examine the effect of introducing sgRNA and repair template into zygotes derived from Cas9-expressing females by electroporation.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown previously that transgenic Cas9-expressing embryo donors can be used effectively for mouse model production, obviating the need to provide exogenous Cas9 [14][15][16] . Maternally contributed Cas9 protein within the fertilized zygote is sufficient for mutagenesis, and only the sgRNA and repair template need be introduced.…”
mentioning
confidence: 99%